Effectivity battle between C-MAC and McGrath® video laryngoscope in a patient with general anesthesia at Sanglah Hospital: A pilot study - Jhoni Pardomuan Pasaribu; Tjokorda Gde Agung Senapathi; Pontisomaya Parami (Neurologico Spinale Medico Chirurgico, 2021)
Background: Intubation is a common essential procedure to maintain the airway during general anesthesia. Various video laryngoscopes (VL) on the market today assist anesthesiologists in improving intubation success rates and also in complicated airway cases. There are two types of VL found in our institution, which are C-MAC and McGrath®. Each of them has its pros and cons, which withdrawn our curiosity to compare their effectiveness. Methods: A pilot study was conducted in our center; we included all patients undergoing general anesthesia with physical status ASA I-III and consent to the study and divide them into two groups, C-MAC and McGrath®. We compare C-MAC and McGrath® VL effectiveness in terms of time for intubation, ease of intubation, total attempt, failure to intubate, Cormack Lehane degree, POGO Score, and hemodynamic stability. Results: A total of 20 patients were intubated with two different VL, ten patients for each group. Both VLs accommodate ease of intubation, and overall first attempt successful intubation, though C-MAC showed better laryngeal and glottic visualization, shorter tracheal intubation times, and less hemodynamic change. Conclusion: C-MAC gives better results in laryngeal and glottic visualization, shorter tracheal intubation times, and less hemodynamic change.